A case of three year child with uncorrected tetralogy of Fallot for drainage of fronto-parietal abscess - Rana, Abhimanyu; Arora, Kishore Kumar; Gill, Rashpal Singh (International Journal of Research in Medical Sciences, 2017)
The Tetralogy Fallot was one of the commonest Right to Left shunting disease in the children. TOF is most common in association with brain abscess (13-70%). This case is of a 3 year old child who had tetralogy of Fallot (uncorrected) and was to be taken for drainage of Fronto-Parietal sub dural abscess via Burr hole. The abscess was drained and patient was shifted with inotropes and ventilator support. In next 24 hours patient improved and supports were gradually withdrawn.